Penerapan Prinsip Akuntabilitas dalam Pelayanan Publik untuk mewujudkan Good Governance - Jabar, Abdul; Yuniarni, Evi (WELFARE STATE Jurnal Hukum, 2025)
The principle of accountability is a key element of good governance in public services, which ensures transparency, responsibility, and legal compliance. Its implementation requires clear regulations, technology such as e-government, and public participation. These regulations provide a clear legal framework to ensure that public services not only meet the needs of the community, but also comply with applicable legal and ethical standards. Accountability is an instrument to ensure that the government acts in accordance with the law and can be monitored by the community. Technology not only increases transparency but also allows the collection of data that can be used to evaluate the performance of public services. In the theory of a state of law, this technology supports the creation of the supremacy of law through a more inclusive and efficient monitoring mechanism. Measuring the principle of accountability also requires active public participation in the evaluation process. The government needs to involve the public through satisfaction surveys, public consultation forums, and interactive dialogues to obtain direct feedback on the quality of services. This participation not only enriches evaluation data, but also strengthens the relationship between the government and the community in creating transparent and participatory governance. Through the synergy of regulations, technology, and public involvement, accountability encourages transparent and effective services while supporting sustainable development and integrity in governance.